SAFETY ENVIRONMENT POLAND TODAY AND IN THE PERSPECTIVE OF 15 YEARS. CLASSICAL TERRORISM AND TERRORISM HAZARD FROM CBRN INFLUENCE FACTORS - Sławomir Kleszcz (Defence Science Review, 2018)
The article discusses selected issues related to the security environment of the Republic of Poland in the perspective of the next decade in a complex geopolitical situation. It indicates the main areas of threats in the global as well as the macro-region of Central Europe. He explains the essence of contemporary terrorism, with a variety of subjectivity, as well as possible directions of threats in classical and unconventional means of destruction.